Transcriptomic characterization of hepatocellular carcinoma with CTNNB1 mutation. - Xiao Ding; Yuan Yang; Baoda Han; Chengzhi Du; Naiqing Xu; Huanwei Huang; Tao Cai; Aiqun Zhang; Ze-Guang Han; Weiping Zhou; Liang Chen (PLoS ONE)
Purpose Hepatocellular carcinoma (HCC) is the sixth most common solid tumor worldwide and the third leading cause of cancer-related death. HCC is a particularly serious threat to the Chinese population. Although many molecular alterations are known to be involved in the tumorigenesis of hepatocytes, no systemic survey has examined the somatic mutations in HCC samples from Chinese patients. Our goal was to elucidate somatic mutations in Chinese HCC patients and investigate the possible molecular mechanisms involved in tumorigenesis. Experimental design A total of 110 hepatitis B virus (HBV)-positive HCC samples and 46 HBV-negative HCC samples were genotyped for hot-spot mutations in the CSF1R, CTNNB1, KRAS, BRAF, NRAS, ERBB2, MET, PIK3CA, JAK1, and SMO genes. The transcriptomes of the CTNNB1 mutation-positive HCC samples from the HBV-positive patients (CB+ HCC) were compared to adjacent non-cancerous livers, and significantly altered genes were functionally validated in vitro. Results CTNNB1 mutations accounted for the majority of the mutations detected in our study. A slightly higher mutation rate was found in the HBV-positive patients than in their negative counterparts. A distinct pattern of CTNNB1 mutation was detected in these two populations, and drastic changes at the transcriptomic level were detected in the CB+ tumors compared to adjacent non-cancerous livers. Potential tumor suppressors (FoxA3 and Onecut1) and oncogenes (MAFG and SSX1) were functionally validated. Conclusions Our work is the first systemic characterization of oncogenic mutations in HCC samples from Chinese patients. Targeting the Wnt-β-catenin pathway may represent a valid treatment option for Chinese HCC patients. Our work also suggests that targeting ONECUT1, FOXA3, SSX1, and MAFG may be a valid treatment option for CTNNB1 mutation positive HCC patients.